An Investigation into Speech Acts Used by Lecturers in English Classroom - Ayu Fitri Anjani; Didin Nuruddin Hidayat; Alek Alek (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The study investigates the various speech acts that lecturers use in a Discourse Analysis classroom. The study attempted to determine which type was most frequently used based on Searle’s theory. The study was conducted by involving two lecturers of Discourse Analysis classroom in the Graduate Program of English Education UIN Jakarta, using a qualitative research design. The data were gathered through Zoom video recordings capturing the nuances of learning sessions and the collection of messages within the WhatsApp class group. Subsequently, the data were transcribed and analysed. The interesting findings revealed; 50% of what lecturers said consisted of commands or directives, 24% were representatives, 13% were commissive, and also 13% were expressive. The results indicated that the most dominant type of speech act was directives (50%). Lecturers predominantly utilized directives to guide students in specific actions, including; asking students to allocate more time to study, suggesting them to read reputable scientific journals, and encouraging students to work gradually on their papers to avoid last-minute rushes. In the end, this research helps to understand how lecturers talk and share ideas in a Discourse Analysis classroom. It also provides insights into how lecturers conduct teaching in that particular class.